'Generation Z' and 'second generation': an agenda for learning from cross-cultural negotiations of the climate crisis in the lives of second generation immigrants. Issue 3 (4th May 2021) - Walker, Catherine
ABSTRACT: Cross-cultural negotiations of environmental knowledge in children and young people's lives have received minimal attention in children's geographies and wider childhood scholarship, despite interests in child and youth environmental concerns and learning that predate the school strikes for climate. This viewpoint articulates an agenda for advancing research in this area in light of youth-led articulations of 'climate crisis', beginning with exploration of how second generation immigrants encounter, interpret and negotiate the climate crisis in everyday life. The viewpoint situates this agenda in academic and popular arguments to diversify and decolonise environmentalism amid increasingly polyvocal responses to the climate crisis.